Penerapan Metode Pembelajaran Bervariatif Untuk Meningkatkan Hasil Belajar - Haholongan Simanjuntak; Rosmala Rosmala (Universitas Asahan, 2023)
The purpose of this study was to find out how the application of various learning methods to the learning outcomes of fifth grade students at SD Negeri 15 Toboali on the area of flat shapes. This research was conducted on fifth grade students of SD Negeri 15 Toboali. After learning that applied various learning methods to the material